KONTRIBUSI PENDAPATAN USAHA KERAJINAN TIKAR PURUN TERHADAP PENDAPATAN PETANI KARET DI DESA BETUNG KECAMATAN SEMENDAWAI BARAT KABUPATEN OKU TIMUR. - Catur Giyanto (Sekolah Tinggi Ilmu Pertanian (STIPER) Belitang, 2015)
The purpose of this study is to: (1) To know the cost and income in the business of handicraft mat in the village of Betung, West Semendawai District, OKU Timur Regency, (2) To know whether the business of handicraft mats deserves to be developed, (3) To Knowing the amount of income contribution of handicraft business mats down to family income in Betung Village, West Semendawai District, OKU Timur Regency. This research was conducted in Betung Village, West Semendawai District, OKU Timur Regency, the research method used was purposive method with the consideration that in Betung Village there are business actor of handicraft mats of purun, the research was conducted in February 2013. This research found that the cost On the business of handicraft mats purun Rp. 600.057.- / month while the income of the business is Rp. 259.943 .- / month. Based on the above analysis shows that the business of woven mat mendong worthy to be developed because the R / C 1.43 > 1. 1. and ROI 43%. The amount of income contribution from the handicraft business mat mats purun by 15.27% which categorized small income contribution to family income.